CASES OF DEFORMITIES IN SOME CULTIVABLE FISHES - Pillai, C Thankappan; Thampy, D M (Indian Journal of Fisheries, 2011)
Three different cases of deformities observed In the cultivable fresh water fishes Calla calla, Labeo rohita and Labeo fimbriatus are reported. Catla catla was showing lordosis, Labeo rohita scoliosis and head deformity and L. fimbriatus vertebral column and mouth deformity. The skeleton of Labeo rohita was not exhibiting any synostis and as such is a developmental deformity. The deformities observed belong to the categories - biological, developmental and nutritional.